Molecular assessments of BRAF, KRAS and relationship with a clinic opathological feature in Sporadic Colorectal Cancer - Basim Mohammed Hanon, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: One of the most prevalent kinds of cancerous tumours seen all over the globe is the sporadic type of CRC, which is also referred to as CRC. Alterations in the oncogenes have a key role in the regulation of cell division, particularly in the context of tumours. These adjustments trigger cell division by sending signals from the exterior of the cell to the nucleus, which is located in the centre of the cell. Objective: The aim of this investigationis to assessment related between the mutations in Kirsten rat sarcoma virus(KRAS), serine/threonine-protein kinase B-Raf (BRAF) genesand sporadic CRC(CRC) disease. Methods: A total of 47 samples from patients (males 53.2% - females 46.8%)with CRC and conventional polymerase chain reaction (cPCR)were used to test all specimens. The study groups were classified according to age into two groups, 1st (G1), patients below 50 years old and 2nd (G2),including ages above 50.The mutation in the BRAFand KRASgenes was selected at 12,13, and 15 codons. Tumours were classified into well, moderate and poorly differentiated, and the site of the tumour was into the right, left,and rectum. Data analysis was performed using the SPSS and GraphPad prism with a significant rate at P. value <0.05. Results: The male and female patients of this study were significantly varied between groups of gender 26 male-21 female (P=0.0149) and age 18 G1 <50 -19 G2>50 years old (P=0.0488). Distribution of the grades in this study was significantly different between groups, well, moderate and poorly differentiated (7, 25 and 15, P.value= 0.0107), and similar findings in the statistics of the tumour site right, left, and rectum (24, 17 and 6, P.value=0.0252). This study recorded 61.7% mutation in KRAS, while 25.53% mutation in BRAF correlated with CRC. Conclusion: we concluded that mutations in the KARAS and BRAF genes mightcorrelate with the CRC incidence in patients from Iraq.